Simulation of Seismic Liquefaction: 1-G Model Testing System and Shaking Table Tests - Ecemiş, Nurhan; Ecemiş, Nurhan (Taylor and Francis Ltd., 2013)
In this paper, we focus on the development and performance of the 1-g model testing system to monitor the liquefaction occurrence of saturated soils, under subsequent one-dimensional shake table tests. The system is composed of one-dimensional laminar box, cone penetration system, soil model, system for hydraulic soil pumping to achieve loose soil deposit, instrumentation and associated testing hardware. In order to simulate the free-field conditions in the laboratory, the laminates slide on each other using rollers placed between each laminate. The static calibration test results demonstrate that the friction effects between the laminates and the rollers are satisfactorily low. The loosest and the most liquefiable sand deposit is prepared inside the laminar box by hydraulic filling process and subjected to four subsequent shaking tests at different intensities. First, the laminar box and shake table performance is verified by using time-histories of acceleration and displacement test results. Then, the measured data inside the soil and on the laminates are compared with the numerical model. The previously calibrated numerical model UBCSAND which shows the seismic loading conditions in the free field is used in the simulations. Those shake table test results and the numerical simulations of the box and the soil indicate that the usefulness of the laminar box system for shaking table tests is satisfactory for dynamic model tests in 1-g gravity.
Keywords: Laminar box; Liquefaction; Shake table test; Soil liquefaction; UBCSAND model